Experimental Study of the Influence of Moisture Content on the Mechanical Properties and Energy Storage Characteristics of Coal. (24th July 2021) - Liu, Nan; Li, Chuanming; Feng, Ruimin; Xia, Xin; Gao, Xiang
Abstract : Rock burst occurs frequently as coal mining depth goes deeper, which seriously impacts the safety production of underground coal mines. Coal seam water injection is a technique commonly used to prevent and control such accidents. Moisture content is a critical factor tightly related to rock burst; however, an in-depth insight is required to discover their relationship. In this study, the influence of moisture content on the mechanical properties of coal and rock burst tendency is explored via multiple measurement techniques: uniaxial compression test, cyclic loading/unloading test, and acoustic emission (AE) test. These tests were performed on coal samples using the MTS-816 rock mechanics servo testing machine and AE system. The testing results showed that with the increase in moisture content, the peak strength and elastic modulus of each coal sample are reduced while the peak strain increases. The duration of the elastic deformation phase in the complete stress-strain curves of coal samples is shortened. As the moisture content increases, the area of hysteretic loop and elastic energy index W ET of each coal sample are reduced, and the impact energy index K E is negatively correlated with the moisture content, whereas dynamic failure time is positively correlated with the moisture content, but this variation trend is gradually mitigated with the continuous increase of moisture content. The failure of the coal sample is accompanied by the sharp increase in the AE ring-down count, whose peak value lags behind the peak stress, and the ring-down count is still generated after the coal sample reached the peak stress. With the increase in moisture content, the failure mode of the coal sample is gradually inclined to tensile failure. The above test results manifested that the strength of the coal sample is weakened to some extent after holding moisture, the accumulative elastic energy is reduced in case of coal failure, and thus, coal and rock burst tendency can be alleviated. The study results can provide a theoretical reference for studying the fracture instability of moisture-bearing coal and prevention of coal and rock burst by the water injection technique.